(untitled) (International journal of artificial intelligence, 2024)
The article provides information about electronic textbooks, continuous improvement of computer technologies, and software educational tools in the organization of the educational process in the current era of globalization. Interactive whiteboards and overhead projectors (ref-projectors), successful use of computers for mastering the necessary programs, organization of technology lessons based on software educational tools, advantages and practical importance of the methodology of developing students' readiness were discussed.